A regional social progress index: the case of Epirus, Greece. (21st July 2020) - Diakomihalis, Mihail
With reference to a social progress index (SPI), this paper considers the progress level of the region of Epirus, Greece, to gain insights into factors affecting different facets of the region's social wellbeing and to identify its socioeconomic strengths and weaknesses. In a sample of respondents representing three levels of education and three types of employment who live in Epirus, the region is empirically evaluated for how satisfying it meets three criteria (i.e., basic human needs, foundations of well-being, and personal and social opportunities) and each of their four sub criteria. Revealing wide variation in the satisfaction of Epirus's mean scores compared to those of wellbeing indices applied worldwide and in Greece, the results informed suggestions for improving Epirus's social progress and for verifying its current development relative to other regions of EU member countries.